Le passage à la royauté de Roger II de Sicile en 1130 : propositions pour l’analyse d’une révolution symbolique - Guilhem Dorandeu-Bureu; Annliese Nef (Tabularia)
This paper aims to demonstrate the usefulness of the Bourdieusian concept of “symbolic revolution” for the analysis of the mutations that crystallised around 1130 in the administration, the art of government, as well as in the artistic and literary sphere in southern Italy and Sicily during the reign of Roger II. It allows us to take into consideration both their radical novelty and their causes referring to regional pasts, shedding light not only on their conceptual dimension, but also their material dimension. The Sicilian framework is privileged here and the demonstration is carried out through the analysis of three cases: the conception of Palermo as a capital, the difficulties raised by the interpretation of the ceiling of the Palatine Chapel of Palermo and the genesis of the rogerian sigillographic uses.